Marketing - Grewal Dhruv (Mc Graw Hill, 2009)
It is clear that marketing has changed significantly in the past few decades. So much so, that in 2004 and again in 2007, the American Marketing Association redefined the word “marketing” itself. Grewal/Levy is the first Principles of Marketing text to be written from the ground up using the new definition and its value focus. In keeping with the value theme of the text, the authors met face to face with more than 150 instructors and walked through each chapter of the text and each supplement of the package in order to provide the most current, useful text and package on the market. Other themes that permeate throughout the text are: services, ethics, global marketing and the power of the internet. Because services marketing and ethics in marketing play such vital roles in marketing practice today, the authors have dedicated an entire chapter to each of these concepts. The authors provide adding value, superior service, ethical and societal dilemmas and the power of the internet examples throughout, and everywhere these themes fit. The authors have also been careful to integrate the 4Ps of marketing with the overriding value theme.